Statistical analysis of risk factors associated with lumbar spine pathologies for the employed population - Mena, Vanessa (2022)
Objective: Determine the risk factors of lumbar pathologies in patients employed and affiliated with the health system, based on physical examination, habits, personal history, and occupational risk factors. Methods: The study design is retrospective, cross-sectional. In a sample of 668 adult workers from Ecuador. The binary logit response predictive model was applied to identify risk factors and supervised learning methodology (classification trees) was used to classify patients according to the degree of lumbar pathology. Results: The logistic predictive model has a sensitivity of 62.5%, a specificity of 63.7%, the area under the ROC curve was 0.63, and precision of 63.4% was determined.   Conclusion: The factors that increase the risk of the most frequent lumbar pathology (low back pain) in order of importance in patients are: younger age, female sex, tend to be exposed to psychosocial risk factors at work, and lower risk of having mechanical factors.